Pengaruh Persepsi Kemudahan, Kepercayaan, Manfaat dan Risiko Terhadap Penggunaan BRI Mobile Pada PT Bank Rakyat Indonesia Di Kabupaten Mimika - Erina Oktavia Safitri; Ignasius Narew (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2023)
This study aims to determine the significance of the effect of percepcions of convenience, trust, benefits and risk on the use of BRI Mobile at PT Bank Rakyat Indonesia in Mimika Regency. The method used by research is the associative method. Data collection techniques carried out by research are observation techniques, documentation, and questionnaires. The analytical tool used in this research is SEM PLS. The result of this study indicate that convenience and trust have to no significant effect on using BRI Mobile at PT Bank Rakyat Indonesia in Mimika Regency, while the benefits and risk have a significant effect on using BRI Mobile at PT Bank Rakyat Indonesia in Mimika Regency.